Poor virus-specific T-cell responses early after tick-borne encephalitis virus infection correlate with disease severity - Amare Aregay; Jan Slunečko; Petra Bogovic; Miša Korva; Katarina Resman Rus; Nataša Knap; Jana Beicht; Mareike Kubinski; Giulietta Saletti; Imke Steffen; Franc Strle; Tatjana Avšič-Županc; et al. (Emerging Microbes and Infections)
Tick-borne encephalitis virus (TBEV) infection may cause acute central nervous system inflammation varying in clinical manifestations and severity. A possible correlation of TBEV-specific antibody and cell-mediated immune responses, shortly after infection, with clinical manifestations, severity and long-term outcome has been poorly investigated. In a cohort of thirty early tick-borne encephalitis (TBE) patients, we assessed the magnitude, specificity and functional properties of TBEV-specific T-cell and antibody responses. These responses early during disease were assessed in view of clinical manifestations, severity and long-term outcome. TBEV-specific T-cell responses to C, E, NS1, and NS5 proteins were significantly lower in patients with severe acute illness than in patients with mild TBE. Lower T-cell responses to E, NS1, and NS5 proteins also correlated with the development of meningoencephalomyelitis. Virus-specific antibody titres early after infection did not correlate with disease severity, clinical manifestations, or long-term outcome in this study, possibly due to the small number of patients of which matching serum and peripheral blood mononuclear cells were available. The findings suggest that virus-specific T cells afford a certain degree of protection against the development of severe TBEV-induced disease.